2014
DOI: 10.1148/radiol.14140088
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of US in Percutaneous Dilatational Tracheostomy: Randomized Controlled Trial and Review of the Literature

Abstract: The use of US guidance before and during PDT percutaneous dilatational tracheostomy could render the procedure easier and safer, with fewer complications but a slightly longer procedure time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 22 publications
1
60
1
3
Order By: Relevance
“…21 Few prospective randomised controlled trials (RCTs) exist but have suggested improved rates of first-pass punctures, midline location and trends towards fewer procedure-related complications, when compared with anatomical landmarkbased PT. 14,16,22,23 In direct comparison with bronchoscopy-aided PT, Ravi et al in a prospective, single-centre randomised control trial (RCT) of 74 PT-related complications rates range from 2.1% to more than 20%. These are usually early and minor, but significant complications related to haemorrhage, false tract formation and hypoxia from airway obstruction can occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Few prospective randomised controlled trials (RCTs) exist but have suggested improved rates of first-pass punctures, midline location and trends towards fewer procedure-related complications, when compared with anatomical landmarkbased PT. 14,16,22,23 In direct comparison with bronchoscopy-aided PT, Ravi et al in a prospective, single-centre randomised control trial (RCT) of 74 PT-related complications rates range from 2.1% to more than 20%. These are usually early and minor, but significant complications related to haemorrhage, false tract formation and hypoxia from airway obstruction can occur.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17]23 Measuring the pretracheal soft-tissue distance can also help determine appropriate tracheostomy length (regular vs. extended). 16,17,22 Additionally, intra-procedural ultrasound may assist in identifying the correct level of puncture between the appropriate tracheal rings, guide midline placement of the needle and assist physicians to avoid vulnerable structures, particularly the thyroid isthmus and aberrant vessels, helping minimise the likelihood of immediate vascular complications. Following the procedure, the ultrasound can help confirm the position and is a faster and more sensitive screening test for pneumothorax than chest radiography.…”
Section: Disclosure Statement -No Potential Conflict Of Interest Wasmentioning
confidence: 99%
“…If ultrasound is available, why not use realtime ultrasound guidance for placement of the needle and guide wire? 8 This will satisfy those practitioners uncomfortable with lack of (bronchoscopy) visualization during needle and guide-wire insertion. Posterior wall puncture is avoided in ultrasound-guided PDT by visualizing the direct progression of the needle into the trachea and by the ability to measure the depth needed for insertion.…”
Section: To the Editormentioning
confidence: 97%
“…Ultrasound guidance allows midline placement in the intended tracheal space with a high degree of accuracy, usually in the first stick. 8 Bronchoscope puncture and ventilation impairment are not issues with this technique. Thus, a DLET is not needed.…”
Section: To the Editormentioning
confidence: 99%
“…Yavuz et al [3], in their randomised controlled trial on 341 patients, reported the use of USG guidance for PCT in only one patient with deviated trachea due to lung fibrosis. To conclude, in difficult scenarios such as deviated trachea, the ability of USG to improve the accuracy of PCT increases considerably, along with the prevention of complications.…”
mentioning
confidence: 99%